The diverse role of the PPARγ coactivator 1 family of transcriptional coactivators in cancer - Girnun, Geoffrey D. (2012)
The critical role that altered cellular metabolism plays in promoting and maintaining the cancer phenotype has received considerable attention in recent years. For many years it was believed that aerobic glycolysis, also known as the Warburg Effect, played an important role in cancer. However, recent studies highlight the requirement of mitochondrial function, oxidative phosphorylation and biosynthetic pathways in cancer. This has promoted interest into mechanisms controlling these metabolic pathways. The PPARγ coactivator (PGC)-1 family of transcriptional coactivators have emerged as key regulators of several metabolic pathways including oxidative metabolism, energy homeostasis and glucose and lipid metabolism. While PGC-1s have been implicated in a number of metabolic diseases, recent studies highlight an important role in cancer. Studies show that PGC-1s have both pro and anticancer functions and suggests a dynamic role for the PGC-1s in cancer. We discuss in this review the links between PGC-1s and cancer, with a focus on the most well studied family member, PGC-1α.